Monogeneans (Dactylogyridae) parasitizing gills of Salminus hilarii from a Neotropical reservoir, Brazil - Brandão, Heleno [UNESP]; Yamada, Fábio Hideki [UNESP]; Toledo, Gislayne De Melo [UNESP]; Carvalho, Edmir Daniel [UNESP]; Silva, Reinaldo José Da [UNESP] (Colégio Brasileiro de Parasitologia Veterinária, 2013)
With the aim of creating an inventory of the metazoan gill parasites of Salminus hilarii in the Taquari River, state of São Paulo, Brazil, five species of monogeneans (Anacanthorus contortus, A. bicuspidatus, Annulotrematoides parisellei, Jainus iocensis and Tereancistrum arcuatus) are reported the first time for this host. A total of 28 fish were sampled quarterly between April 2011 and January 2012, with 10 hosts in a lentic ecosystem and 18 in a lotic ecosystem. Quantitative ecological descriptors (prevalence, intensity of infestation and abundance) were calculated for the purpose to comparing the two ecosystems sampled (lentic and lotic ecosystems). However, no quantitative difference between the lentic and lotic ecosystems was observed. The present study has made available a checklist for species of the genus Anacanthorus and their hosts and geographical distribution in the Neotropical region up to the present time.

Com o objetivo de inventariar os metazoários parasitos de brânquias de Salminus hilarii do rio Taquari, estado de São Paulo, Brasil, cinco espécies de monogenéticos (Anacanthorus contortus, A. bicuspidatus, Annulotrematoides parisellei, Jainus iocensis, e Tereancistrum arcuatus) foram registradas pela primeira vez para o presente hospedeiro. Um total de 28 peixes foi amostrado trimestralmente entre abril/2011 e janeiro/2012, com 10 hospedeiros no ecossistema lêntico e 18 no ecossistema lótico. Os descritores ecológicos quantitativos (prevalência, intensidade de infestação e abundância) foram calculados com o objetivo de comparar os dois ecossistemas amostrados (ecossistema lêntico versus ecossistema lótico). No entanto, nenhuma diferença quantitativa desses foi verificada entre os ecossistemas lêntico e lótico. O presente estudo disponibiliza uma lista de espécies do gênero Anacanthorus, os hospedeiro e distribuição geográfica na região Neotropical até o presente momento.
Monogenéticos (Dactylogyridae) parasitando brânquias de Salminus hilarii de uma represa Neotropical, Brasil
Keywords: Ectoparasite; Monogenea; freshwater fish; Taquari River; Ectoparasito; Monogenea; peixe de água doce; rio Taquari